Bulgaria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on Bulgaria investigates possible driving forces behind the investment boom based on cross-country evidence. The diagnosis of the drivers behind the investment boom is important as it is key to assessing Bulgaria's economic prospects, vulnerabilities, and policy challenges. The available evidence is less than clear-cut, but broadly suggests that the investment boom reflects to a large extent a one-off reassessment of Bulgaria's riskiness as an investment location. The paper also investigates why Bulgaria's GDP growth rate did not respond more strongly to the investment boom.